2010
DOI: 10.1136/jamia.2010.003673
|View full text |Cite
|
Sign up to set email alerts
|

Health information exchange: persistent challenges and new strategies: Table 1

Abstract: Recent federal policies and actions support the adoption of health information exchange (HIE) in order to improve healthcare by addressing fragmented personal health information. However, concerted efforts at facilitating HIE have existed for over two decades in this country. The lessons of these experiences include a recurrence of barriers and challenges beyond those associated with technology. Without new strategies, the current support and methods of facilitating HIE may not address these barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
201
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(204 citation statements)
references
References 26 publications
1
201
0
2
Order By: Relevance
“…While the data are even sparser, trade reports and some research indicated that the enterprise HIE approach has also grown rapidly (Harris Healthcare Solutions, 2012). This difference in trajectories within the population of HIOs (described in detail by Lenert et al, 2012;Rubin, 2003;Vest & Gamm, 2010) suggests the possibility of selection forces at work.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…While the data are even sparser, trade reports and some research indicated that the enterprise HIE approach has also grown rapidly (Harris Healthcare Solutions, 2012). This difference in trajectories within the population of HIOs (described in detail by Lenert et al, 2012;Rubin, 2003;Vest & Gamm, 2010) suggests the possibility of selection forces at work.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Population ecology allows for individual organizations to evolve, adapt, and even cooperate in response to environmental pressures overtime (Singh & Lumsden, 1990). HIOs have changed over time to meet the expectations of the environment (Vest & Gamm, 2010) and have created partnerships in attempts to position themselves within the market for information exchange service (see, for the most recent example, the cooperation between Carequality and CommonWell). Additionally, some changes to HIOs are isomorphic, suggesting the action of institutional pressures in the environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Our study addresses this gap by exploring the association between the key factors and HIE usage by ambulatory care providers. Our research objectives are twofold: (1) [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Even among those shared data, providers can restrict the type and amount of healthcare information that is shared [21].…”
Section: Introductionmentioning
confidence: 99%
“…Health information exchanges (HIEs) require a synthesis of goals, protocols, data formats, and infrastructure within and across organizations. The partners in a HIE are likely to think of, and govern themselves as, stand-alone entities and may have very different institutional cultures and practices [3][4][5]. When the data to be exchanged happen to be HIV-related, the potential barriers are further complicated by legal and organizational precedents that place primacy on the protection and limited distribution of health information in light of historical-and, to a lesser degree, continuing-stigmatization of the disease [6].…”
Section: Introductionmentioning
confidence: 99%